PENGUJIAN KANDUNGAN BAKTERI Salmonella sp. PADA IKAN TUNA (Thunnus sp.) MENGGUNAKAN METODE Real-time PCR (Polymerase Chain Reaction) - Iftachul Farida; Desi Febrianti; I Gede Ivan Ari Dewa Mahaputra (Fisheries Product Technology Department, Faculty of Marine Science and Fisheries, Universitas Maritim Raja Ali Haji, 2023)
Fish is a commodity that decomposes easily and quickly (high perishable food) because it contains protein and water which is quite high, so it requires quick, clean, careful and cool handling (quick, clean, careful and cool). Poor handling caused fish to be easily contaminated with pathogenic bacteria, one of which was Salmonella sp. This study used fresh and processed tuna samples in Denpasar, Bali. The purpose of this study was to detect Salmonella sp. on tuna using real-time PCR method. In addition, to strengthen the test results for Salmonella sp. using real-time PCR, sensory testing was also carried out on appearance, texture, and smell. The test results showed that one sample of tuna was indicated to contain Salmonella sp., this was because the sample had reached a Threshold Cycle (Ct) value of 22.11 through the amplification curve. These results was supported by the results of sensory testing performed on samples that were positive for Salmonella sp. The average sensory value was 26.5 in the Mid Pass category.